Quality of qualitative studies centred on patients in family practice: a systematic review - Cambon, Benoit; Vorilhon, Philippe; Michel, Laurence; Cadwallader, Jean-Sébastien; Aubin-Auger, Isabelle; Pereira, Bruno; Vaillant Roussel, Hélène (Family practice, 2016)
Qualitative research is often used in the field of general medicine. Our objective was to evaluate the quality of published qualitative studies conducted using individual interviews or focus groups centred on patients monitored in general practice. We have undertaken a review of the literature in the PubMed and Embase databases of articles up to February 2014. The selection criteria were qualitative studies conducted using individual interviews or focus groups, centred on patients monitored in general practice. The articles chosen were analysed and evaluated using a score established from the Relevance, Appropriateness, Transparency and Soundness (RATS) grid. The average score of the 52 studies chosen was 28 out of 42. The criteria least often present were the description of the patients who chose not to participate in the study, the justification of the end of data collection, the discussion of the influence of the researchers and the discussion of the confidentiality of the data. The criteria most frequently described were an explicit research question, justified and in relation to existing knowledge, the agreement of the ethical committee and the presence of quotations. The number of studies and the score increased from year-to-year. The score was independent of the impact factor of the journal. Even though the qualitative research was published in reviews with a low impact factor, our results suggest that this research responded to the quality criteria of the RATS grid. The evaluation scored using RATS could be useful for authors or reviewers and for literature reviews.